Neutralization of toxicological activities of medically-relevant Bothrops snake venoms and relevant toxins by two polyvalent bothropic antivenoms produced in Peru and Brazil - Estevao-Costa M.I. (2016)
Snakebite envenoming is a neglected public pathology, affecting especially rural communities or isolated areas of tropical and subtropical Latin American countries. The parenteral administration of antivenom is the mainstay and the only validated treatment of snake bite envenoming. Here, we assess the efficacy of polyspecific anti-Bothrops serum (α-BS) produced in the Instituto Nacional de Salud (INS, Peru) and at the Fundação Ezequiel Dias (FUNED, Brazil), to neutralize the main toxic activities induced by five medically-relevant venoms of: Bothrops atrox, B. barnetti, and B. pictus from Peru, and the Brazilian B. jararaca and B. leucurus, all of them inhabiting different geographical locations.